COGNITIVE AND EMOTIONAL PREDICTORS OF BULLYING BEHAVIOR IN PRIMARY SCHOOL CHILDREN - Berdiyeva Gulmira Juraevna; Rabitova Sevinch Ulug'bek qizi (Innovate Conferences, 2025)
This study explores the relationship between cognitive development, emotional intelligence, and the occurrence of bullying in primary school children. Based on research conducted in four public schools involving 106 children aged 7 to 11, the study examines how self-awareness, empathy, impulse control, and problem-solving skills influence bullying behavior. The results indicate that children with low emotional intelligence and weak executive function are more likely to display aggressive tendencies or become frequent victims. The findings underscore the importance of enhancing emotional literacy and cognitive flexibility to mitigate bullying.
Keywords: bullying, cognitive development, emotional intelligence, problem-solving, child psychology, primary education